EFFECT OF DIETARY PROBIOTIC SUPPLEMENTATION ON GROWTH PERFORMANCE, SURVIVAL RATE, AND CONDITION FACTOR OF RED NILE TILAPIA (Oreochromis niloticus L.) - Aulia, Deni; Harahap, Kurnia Sada; Indrayati, Artin (Jurnal Perikanan Unram, 2025)
Red Nile Tilapia (Oreochromis niloticus L.) is one of the important commodities in aquaculture, possessing high economic value and promising prospects for supporting the economy and food security. Various efforts have been made to increase fish production, one of which is through the use of feed additives. Probiotics have been widely used in aquaculture, either as a feed supplement or applied directly to the culture media. This study aims to compare the growth, survival rate, and condition factor of Red Nila Tilapia fed with probiotic-supplemented feed and those without probiotics. The study was conducted over 84 days using Red Nila Tilapia measuring 6.8 cm, stocked in earthen ponds at a density of 10 fish/m². The results showed that Red Nila Tilapia fed with probiotic-supplemented feed had a higher growth performance compared to those without probiotics. The average daily growth rate and survival rate of fish given probiotics were 2.06 g/day and 87%, respectively, whereas fish without probiotic supplementation had 1.70 g/day and 84%. Conversely, fish fed with probiotics exhibited a condition factor of 1.06, which was lower than the 1.69 recorded in fish without probiotics. The findings of this study indicate that probiotics can be used as a feed additive for Red Nile Tilapia, providing positive effects on growth, survival rate, and fish health.